2021
DOI: 10.1101/2021.10.04.463138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linking individual differences in human primary visual cortex to contrast sensitivity around the visual field

Abstract: The size and organization of primary visual cortex (V1) varies across individuals. Across individuals, V1 size varies more than twofold. Within individuals, cortical magnification varies with eccentricity and polar angle. Contrast sensitivity has been hypothesized to be limited by cortical resources, and specifically by the number of activated V1 neurons. Here, we quantify the relation between contrast sensitivity and V1 cortical magnification as a function of both individual observers and polar angle. We meas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 121 publications
(227 reference statements)
2
7
0
Order By: Relevance
“…However, a computational observer model has shown that these retinal asymmetries only account for a small proportion of behavioral contrast sensitivity asymmetries ( Kupers et al., 2019 , 2022 ). These asymmetries also exist and are greatly amplified, in the distribution of cortical surface area in the primary visual cortex, where there is substantially less surface dedicated to processing the upper vertical meridian than the lower vertical meridian ( Benson et al., 2021 ; Himmelberg et al., 2021a , b ). Thus, there is a reduction in neural resources allocated to the upper vertical meridian that could likely explain poorer visual performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, a computational observer model has shown that these retinal asymmetries only account for a small proportion of behavioral contrast sensitivity asymmetries ( Kupers et al., 2019 , 2022 ). These asymmetries also exist and are greatly amplified, in the distribution of cortical surface area in the primary visual cortex, where there is substantially less surface dedicated to processing the upper vertical meridian than the lower vertical meridian ( Benson et al., 2021 ; Himmelberg et al., 2021a , b ). Thus, there is a reduction in neural resources allocated to the upper vertical meridian that could likely explain poorer visual performance.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast sensitivity, a fundamental visual capability, declines across eccentricity 1 and varies with polar angle: sensitivity is higher along the horizontal than vertical meridian –HorizontalVertical Anisotropy (HVA)– and along the lower than upper vertical meridian –Vertical Meridian Asymmetry (VMA) 27 . Cortical magnification, the linear extent of cortex corresponding to one degree of visual angle (mm/°), declines with eccentricity 8 and links behavior to brain structure 912 (‘Quantitative’ hypothesis).…”
Section: Mainmentioning
confidence: 99%
“…For fixed-size and M-scaled gratings, the VMA extent reached a maximum of 40% at 1 cpd in the parafovea and 8 cpd in the perifovea. The VMA had only been characterized at eccentricities >2° 24,6,7 . This near-foveal location reveals that the SF at which the VMA peaks depends on eccentricity.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that individual variation in the distribution (as opposed to overall quantity) of retinal cell populations over eccentricity or polar angle may be reflected in the visual cortex. Indeed, recent work has shown that polar angle variation in group and individual measures of perception are related to variation in cortical magnification across area V1 (Benson et al, 2021;Himmelberg, et al, 2021;Kupers et al, 2022).…”
Section: Rgc Influence Declines Along the Visual Pathwaymentioning
confidence: 99%